Evolution of Friction and Permeability in a Propped Fracture under Shear. (4th December 2017) - Zhang, Fengshou; Fang, Yi; Elsworth, Derek; Wang, Chaoyi; Yang, Xiaofeng
Abstract : We explore the evolution of friction and permeability of a propped fracture under shear. We examine the effects of normal stress, proppant thickness, proppant size, and fracture wall texture on the frictional and transport response of proppant packs confined between planar fracture surfaces. The proppant-absent and proppant-filled fractures show different frictional strength. For fractures with proppants, the frictional response is mainly controlled by the normal stress and proppant thickness. The depth of shearing-concurrent striations on fracture surfaces suggests that the magnitude of proppant embedment is controlled by the applied normal stress. Under high normal stress, the reduced friction implies that shear slip is more likely to occur on propped fractures in deeper reservoirs. The increase in the number of proppant layers, from monolayer to triple layers, significantly increases the friction of the propped fracture due to the interlocking of the particles and jamming. Permeability of the propped fracture is mainly controlled by the magnitude of the normal stress, the proppant thickness, and the proppant grain size. Permeability of the propped fracture decreases during shearing due to proppant particle crushing and related clogging. Proppants are prone to crushing if the shear loading evolves concurrently with the normal loading.